Training Children to Perceive Non-native Lexical Tones: Tone Language Background, Bilingualism, and Auditory-Visual Information - Kasisopa, Benjawan; El-Khoury Antonios, Lamya; Jongman, Allard; Sereno, Joan A.; Burnham, Denis (Frontiers in Psychology, 2018)
This study investigates the role of language background and bilingual status in the perception of foreign lexical tones. Eight groups of participants, consisting of children of 6 and 8 years from one of four language background (tone or non-tone) x bilingual status (monolingual or bilingual) – Thai monolingual, English monolingual, English-Thai bilingual, and English-Arabic bilingual were trained to perceive the four Mandarin lexical tones. Half the children in each of these eight groups were given auditory-only (AO) training and half auditory-visual (AV) training. In each group Mandarin tone identification was tested before and after (pre- and post-) training with both auditory-only test (ao-test) and auditory-visual test (av test). The effect of training on Mandarin tone identification was minimal for 6-year-olds. On the other hand, 8-year-olds, particularly those with tone language experience showed greater pre- to post-training improvement, and this was best indexed by ao-test trials. Bilingual versus monolingual background did not facilitate overall improvement due to training, but it did modulate the efficacy of the Training mode: for bilinguals both AO and AV training, and especially AO, resulted in performance gain; but for monolinguals training was most effective with AV stimuli. Again this effect was best indexed by ao-test trials. These results suggest that tone language experience, be it monolingual or bilingual, is a strong predictor of learning unfamiliar tones; that monolinguals learn best from AV training trials and bilinguals from AO training trials; and that there is no metalinguistic advantage due to bilingualism in learning to perceive lexical tones.